Application of ethanol alleviates heat damage to leaf growth and yield in tomato - Todaka, Daisuke; Quynh, Do Thi Nhu; Tanaka, Maho; Utsumi, Yoshinori; Utsumi, Chikako; Ezoe, Akihiro; Takahashi, Satoshi; Ishida, Junko; Kusano, Miyako; Kobayashi, Makoto; Saito, Kazuki; Nagano, Atsushi J.; et al. (Frontiers in Plant Science, 2024)
Chemical priming has emerged as a promising area in agricultural research. Our previous studies have demonstrated that pretreatment with a low concentration of ethanol enhances abiotic stress tolerance in Arabidopsis and cassava. Here, we show that ethanol treatment induces heat stress tolerance in tomato (Solanum lycopersicon L.) plants. Seedlings of the tomato cultivar 'Micro-Tom' were pretreated with ethanol solution and then subjected to heat stress. The survival rates of the ethanol-pretreated plants were significantly higher than those of the water-treated control plants. Similarly, the fruit numbers of the ethanol-pretreated plants were greater than those of the watertreated ones. Transcriptome analysis identified sets of genes that were differentially expressed in shoots and roots of seedlings and in mature green fruits of ethanolpretreated plants compared with those in water-treated plants. Gene ontology analysis using these genes showed that stress-related gene ontology terms were found in the set of ethanol-induced genes. Metabolome analysis revealed that the contents of a wide range of metabolites differed between water-and ethanol-treated samples. They included sugars such as trehalose, sucrose, glucose, and fructose. From our results, we speculate that ethanol-induced heat stress tolerance in tomato is mainly the result of increased expression of stress-related genes encoding late embryogenesis abundant (LEA) proteins, reactive oxygen species (ROS) elimination enzymes, and activated gluconeogenesis. Our results will be useful for establishing ethanol-based chemical priming technology to reduce heat stress damage in crops, especially in Solanaceae.